New Insight into the Evolution of Symbiotic Genes in Black Locust-Associated Rhizobia. (13th June 2019) - Liu, Zhenshan; Chen, Weimin; Jiao, Shuo; Wang, Xinye; Fan, Miaochun; Wang, Entao; Wei, Gehong
Abstract: Nitrogen fixation in legumes occurs via symbiosis with rhizobia. This process involves packages of symbiotic genes on mobile genetic elements that are readily transferred within or between rhizobial species, furnishing the recipient with the ability to interact with plant hosts. However, it remains elusive whether plant host migration has played a role in shaping the current distribution of genetic variation in symbiotic genes. Herein, we examined the genetic structure and phylogeographic pattern of symbiotic genes in 286 symbiotic strains of Mesorhizobium nodulating black locust ( Robinia pseudoacacia ), a cross-continental invasive legume species that is native to North America. We conducted detailed phylogeographic analysis and approximate Bayesian computation to unravel the complex demographic history of five key symbiotic genes. The sequencing results indicate an origin of symbiotic genes in Germany rather than North America. Our findings provide strong evidence of prehistoric lineage splitting and spatial expansion events resulting in multiple radiations of descendent clones from founding sequence types worldwide. Estimates of the timescale of divergence in North American and Chinese subclades suggest that black locust-specific symbiotic genes have been present in these continent many thousands of years before recent migration of plant host. Although numerous crop plants, including legumes, have found their centers of origin as centers of evolution and diversity, the number of legume-specific symbiotic genes with a known geographic origin is limited. This work sheds light on the coevolution of legumes and rhizobia.